2009
DOI: 10.1002/jcb.22032
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of the lipoidic‐liquiform pro‐vitamin C tetra‐isopalmitoyl‐ascorbate (VC‐IP) against ultraviolet‐A ray‐induced injuries in human skin cells together with collagen retention, MMP inhibition and p53 gene repression

Abstract: Irradiation with ultraviolet-A (UVA) ray at doses of 20-100 J/cm(2) diminished the cell viability of human keratinocytes HaCaT and human melanoma cells HMV-II, both of which were protected by pre-irradiational administration with the ascorbic acid (Asc) derivative, VC-IP (2,3,5,6-O-tetra-2'-hexyldecanoyl-L-ascorbic acid; vitamin C-isopalmityl tetraester), which is the first lipoidic-liquiform pro-vitamin C by itself that is materialized by esterization of all four intramolecular hydroxyl groups of an Asc molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Matsuda et al (2008) reported that VCP-IS-2Na inhibited melanogenesis in human melanoma cells and epidermal melanocytes. In addition, Xiao et al (2009) reported that 2,3,5,6-O-tetra-2'-hexyldecanoyl L-ascorbic acid in a liquid form showed cytoprotective effects against UV-A ray-induced injuries in human skin cells. Saitoh et al (2009) reported that a fucoidan-vitamin C complex suppressed tumor invasion through the basement membrane via decreased oxidative stress and metalloproteinase activity in human fibrosarcoma cells.…”
Section: Vc Derivatives In Other Areas Of Skin Health Care and Treatmentioning
confidence: 97%
“…Matsuda et al (2008) reported that VCP-IS-2Na inhibited melanogenesis in human melanoma cells and epidermal melanocytes. In addition, Xiao et al (2009) reported that 2,3,5,6-O-tetra-2'-hexyldecanoyl L-ascorbic acid in a liquid form showed cytoprotective effects against UV-A ray-induced injuries in human skin cells. Saitoh et al (2009) reported that a fucoidan-vitamin C complex suppressed tumor invasion through the basement membrane via decreased oxidative stress and metalloproteinase activity in human fibrosarcoma cells.…”
Section: Vc Derivatives In Other Areas Of Skin Health Care and Treatmentioning
confidence: 97%
“…Notably, miR-21 expression has been associated with exposure to diesel exhaust linked to increased plasma levels of 8-hydroxy-deoxyguanosine (8-OHdG) [ 238 ]. 8-OHdG is induced in DNA by oxidative stress and UV irradiation [ 239 ]. Indeed, melanoma patients with low expression of nuclear 8-OHdG have significantly longer survival times compared to those with high expression [ 240 ].…”
Section: Pollution-mediated Upregulation Of Mir-21mentioning
confidence: 99%
“…Keratinocytes appear to be not only primary sensors of stressful conditions but also major players of the extremely complex immune response in the skin conducting an orchestrated recruitment and functions of other immune cells involved in a stress-inflammation skin reaction [4]. Therefore cultured keratinocytes have become a prototype model for screening of anti-inflammatory, photo-protective, and cancer preventive substances for topical application [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%